Between assistance and misconduct: Generative AI, epistemic integrity, and the future of mathematics education research in Journal on Mathematics Education - Zulkardi; Prahmana, Rully Charitas Indra (Journal on Mathematics Education, 2026)
This editorial examines the role of generative artificial intelligence (GenAI) in reshaping the ecology of scholarly writing in mathematics education, with particular attention to the Journal on Mathematics Education (JME). Grounded in the Indonesian context—where most JME authors are doctoral students navigating pressures to publish in English—the piece highlights how GenAI simultaneously functions as a linguistic lifeline and a potential trap that obscures the intellectual labor of research. Drawing on JME's GenAI policy, we argue that journals must protect the core of intellectual work while acknowledging the unequal access to AI tools across institutions and regions. The editorial discusses epistemic risks such as the erasure of authors' "thinking traces" and the emergence of hallucinated references, illustrated by a recent case in which a submission to JME contained fictitious citations generated by GenAI. It then frames JME as a "patch" in the global knowledge ecology, suggesting that GenAI can be leveraged to broaden participation only if its use is transparent, critically monitored, and embedded within practices of ethical mentoring, especially for doctoral writers. We conclude by inviting the JME community—authors, reviewers, and editors—to cultivate educational uses of GenAI that foster critical hope, epistemic justice, and collective responsibility for the future of mathematics education research.